Economic Burdens of Uncomplicated Malaria in Primary Health Care (PHC) Facilities of Plateau State, Nigeria: Patients' Perspectives - Nahlah, Elkudssiah Ismail; Nanloh, Samuel Jimam; Goh, Khang Wen; Tan, Ching Siang; Long, Chiau Ming * (MDPI, 2023)
Objectives: This study aims at evaluating the costs incurred by patients in Primary Healthcare facilities of Plateau State, Nigeria, due to uncomplicated malaria management. Methods: Patients’ information on resources used and absence from the labour market due to uncomplicated malaria illness were collected using the self-reported cost of illness instruments across 24 selected Primary Health Care (PHC) facilities in Plateau State. The collated data were used to estimate the direct medical and non-medical costs incurred by patients through the summation of the various costs paid out of pocket for the services; while the indirect cost was estimated using the human capital theory. All analyses were conducted through Microsoft Excel and IBM Statistical Package for Social Sciences (SPSS®) version 23 software. Results: The average direct cost per episode of uncomplicated malaria was estimated at NGN 2808.37/USD 7.39, while the indirect average money equivalence of the time lost due to the ailment was estimated at NGN 2717/USD 7.55, giving an average cost of treating uncomplicated malaria borne by patients in Plateau State per episode to be NGN 5525.37/USD 14.94. The projected annual cost of the disease was NGN 9, 921,671,307.22 (USD 27, 560,198.08). Conclusions: The study showed substantial financial costs borne by patients due to uncomplicated malaria in Plateau State, comprising 50.83% of direct cost and 49.17% of the indirect cost of medications.